Pengaruh tingkat inflasi terhadap nilai tukar rupiah (Studi pada Bank Indonesia periode tahun 2011-2015) - Yati Wijayanti Sudarmiani (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2017)
This study aimed to analyze the influence of the inflation rate of the Rupiah. Population and samples used in this study are all monthly time series data rate of inflation and the Rupiah during the period January 2011-December 2015 as many as 60. The data used are secondary data obtained from the official website of Bank Indonesia (www.bi.co.id). The analytical method used in this study is a simple linear regression analysis. The result of the coefficient of determination (r2) which shows that the percentage of the effect of the inflation rate to changes in the rupiah exchange rate of 7,9%. From the calculations, the equation Y = 3.941 + 0,073X , it can be concluded that the level of inflation is positive and significant effect on the rupiah.